2000
DOI: 10.1074/jbc.m001064200
|View full text |Cite
|
Sign up to set email alerts
|

3-Methyladenine-DNA Glycosylase (MPG Protein) Interacts with Human RAD23 Proteins

Abstract: Human 3-methyladenine-DNA glycosylase (MPG protein) initiates base excision repair by severing the glycosylic bond of numerous damaged bases. In comparison, homologues of the Rad23 proteins (hHR23) and the hXPC protein are involved in the recognition of damaged bases in global genome repair, a subset of nucleotide excision repair. In this report, we show that the hHR23A and -B also interact with the MPG protein and can serve as accessory proteins for DNA damage recognition in base excision repair. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
1
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 59 publications
3
66
1
3
Order By: Relevance
“…It is possible that the abortive ⑀C⅐ANPG complex, inaccessible to BER proteins, could be processed by other DNA repair systems. For example, it has been demonstrated that the hHR23A and -B proteins, which are involved in the recognition of DNA damage in global genome-nucleotide excision repair (GG-NER) (56), interact with ANPG and elevate the rate of Hx excision (57). Therefore, the ⑀C⅐ANPG complex may direct ⑀C removal to the GG-NER pathway by recruiting the XPC⅐hHR23B complex to ⑀C via an hHR23B⅐ANPG interaction.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the abortive ⑀C⅐ANPG complex, inaccessible to BER proteins, could be processed by other DNA repair systems. For example, it has been demonstrated that the hHR23A and -B proteins, which are involved in the recognition of DNA damage in global genome-nucleotide excision repair (GG-NER) (56), interact with ANPG and elevate the rate of Hx excision (57). Therefore, the ⑀C⅐ANPG complex may direct ⑀C removal to the GG-NER pathway by recruiting the XPC⅐hHR23B complex to ⑀C via an hHR23B⅐ANPG interaction.…”
Section: Discussionmentioning
confidence: 99%
“…This inverted mode of DNA quality control presents the obvious advantage that the initial sensor does not need to recognize the adducts themselves and, as outlined before, actually avoids close contacts with damaged residues. The general affinity for destabilized DNA sites may facilitate other excision repair processes, as XPC has been shown to interact with 3-methyladenine DNA glycosylase [49], thymine DNA glycosylase [50] and 8-oxoguanine DNA glycosylase [6]. It is relevant to note that even a subtle 8-oxoguanine lesion perturbs the thermodynamic stability of the duplex [51].…”
Section: The Molecular Basis For Substrate Versatilitymentioning
confidence: 99%
“…␤-Pol null cells were transfected with either pIRESneo or pIRESneo͞AAG, and stable populations of cells were selected with G418 (600 g͞ml). G418-resistant cultures were analyzed by Western blotting as described (20) with an AAG-specific polyclonal antibody kindly provided by Timothy R. O'Connor, City of Hope National Medical Center, Duarte, CA (25). Functional glycosylase assays were as described (26) by using a hypoxanthine containing double-stranded oligonucleotide (Trevigen, Gaithersburg, MD).…”
Section: Determination Of Mutant Frequency Atmentioning
confidence: 99%